Differences in the Transcriptomic Response of Campylobacter coli and Campylobacter lari to Heat Stress - Riedel, Carolin; Förstner, Konrad U.; Püning, Christoph; Alter, Thomas; Sharma, Cynthia M.; Gölz, Greta (Frontiers in Microbiology, 2020)
Abstract Campylobacter spp. are one of the most important food-borne pathogens, which are quite susceptible to environmental or technological stressors compared to other zoonotic bacteria. This might be due to the lack of many stress response mechanisms described in other bacteria. Nevertheless, Campylobacter is able to survive in the environment and food products. Although some aspects of the heat stress response in Campylobacter (C.) jejuni are already known, information about the stress response in other Campylobacter species are still scarce. In this study, the stress response of C. coli and C. lari to elevated temperatures (46°C) was investigated by survival assays and whole transcriptome analysis. None of the strains survived at 46°C for more than 8 hours and approx. 20 % of the genes of C. coli RM2228 and C. lari RM2100 were differentially expressed. The transcriptomic profiles showed enhanced gene expression of several chaperones like dnaK, groES, groEL and clpB in both strains, indicating a general involvement in the heat stress response within the Campylobacter species. However, the pronounced differences in the expression pattern between C. coli and C. lari suggest that stress response mechanisms described for one Campylobacter species might be not necessarily transferable to other Campylobacter species.